Integration of Technology and Media in IPAS Learning in Grade IV Elementary School - Suryani, Lilis; Rahmadonna, Sisca; Dwita Haliem, Theresa (International Journal of Elementary Education, 2025)
The integration of technology and media in IPAS learning at the elementary school level has begun to be developed by teachers, thus requiring further analysis of its implementation. Therefore, the purpose of this study is to analyze the implementation of IPAS learning development that integrates technology and media in elementary schools, viewed through the ASSURE model. This study employed a qualitative approach with a descriptive method, using data from classroom observation sheets, response questionnaires from 20 fourth-grade students, interviews with one IPAS teacher, as well as document analysis of IPAS Phase B learning outcomes and the fourth-grade teaching module for Chapter 6. The data were then analyzed using Creswell's qualitative data analysis procedures, starting from raw data collection, organization, comprehensive reading, coding, development of themes and descriptions, to interpretation and validation through triangulation and participant confirmation. The findings show that the implementation of the ASSURE model in IPAS learning has been carried out effectively by the teacher. Based on the results, nearly 95% of the ASSURE syntax has been optimally implemented. These results imply that teachers are capable of designing resource utilization syntax more effectively, which in turn minimizes obstacles in the use of learning media and its supporting tools, and supports the achievement of learning objectives optimally.